1989
DOI: 10.1073/pnas.86.5.1648
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of growth of human mammary tumor cells by potent antagonists of luteinizing hormone-releasing hormone.

Abstract: Various studies support the view that analogs of luteinizing hormone-releasing hormone (LH- des-Gly10-[D-Ser(tBu)6]LH-RH ethylamide (buserelin) had no effect. The antagonists SB-29 and SB-30 also inhibited the rate of cell growth, as measured by cell number, while the LH-RH agonist buserelin had no significant effect. These results support the concept that these new LH-RH antagonists can directly inhibit the growth of human mammary tumors and thus might be suitable for the treatment of breast cancer.RHChronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(33 citation statements)
references
References 17 publications
2
30
0
1
Order By: Relevance
“…It has also been reported that treatment of thymocytes, splenocytes, and lymphocytes with GnRH and its analogues increased their proliferative activity (Marchetti et al ., 1989;Batticane et al ., 1991;Azad et al ., 1997). In these studies the effects of GnRH on cell proliferation were investigated by measuring tumor weight and/or volume, the rate of cell proliferation, or 3 H-thymidine incorporation (Redding and Schally, 1983;Sharoni et al ., 1989;Pati and Habibi, 1995;Dondi et al ., 1998). However, to our knowledge, there have been no studies that compared stimulatory with inhibitory effects.…”
Section: Effects Of Gnrh On Colony-formation 1-stimulatory and Inhibimentioning
confidence: 99%
“…It has also been reported that treatment of thymocytes, splenocytes, and lymphocytes with GnRH and its analogues increased their proliferative activity (Marchetti et al ., 1989;Batticane et al ., 1991;Azad et al ., 1997). In these studies the effects of GnRH on cell proliferation were investigated by measuring tumor weight and/or volume, the rate of cell proliferation, or 3 H-thymidine incorporation (Redding and Schally, 1983;Sharoni et al ., 1989;Pati and Habibi, 1995;Dondi et al ., 1998). However, to our knowledge, there have been no studies that compared stimulatory with inhibitory effects.…”
Section: Effects Of Gnrh On Colony-formation 1-stimulatory and Inhibimentioning
confidence: 99%
“…The presence of LH-RH receptors in ovarian cancer suggests that LH-RH analogs could exert direct inhibitory effects on the growth of ovarian cancers (11). Previously, some direct action of LH-RH analogs was also proposed in the case of prostate and breast cancers (22)(23)(24).…”
mentioning
confidence: 99%
“…These experimental results suggest a regulatory role for LHRH-like peptides on tumor growth (14,18,21,27,28). Consequently LHRH antagonists like Cetrorelix could be considered for the development of new therapies for LHRH receptor positive cancers (17).…”
Section: Introductionmentioning
confidence: 89%
“…This concept is supported by an inhibitory effect of LHRH agonists and LHRH antagonist Cetrorelix on human mammary, prostatic, ovarian and endometrial cancer cell lines in vitro through specific tumoral LHRH receptors under conditions which exclude effects through the pituitary and the gonads (14,15,(18)(19)(20). Particularly relevant could be the demonstration of the inhibitory effects of Cetrorelix on growth of MDA-MB-231 and MCF-7 human breast cancer cells in vitro (21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%